Iron stores in pregnant women with sickle cell disease: a protocol for a systematic review and meta-analysis. Issue 9 (9th September 2019) - Aroke, Desmond; Momo Kadia, Benjamin; Njim, Tsi
Abstract : Introduction: Sickle cell disease (SCD) is the most common inherited disease worldwide. The greatest disease burden is seen in sub-Saharan Africa. Early diagnosis and improved care of people living with SCD have led to an increase in the number of women with SCD reaching the reproductive age. Iron deficiency anaemia remains the most common cause of anaemia in pregnancy, affecting 51%–63% of pregnancies in Africa. However, the unavailability of guidelines on supplementation of iron in this pregnant subpopulation often leaves clinicians in a fix. We propose to conduct the first systematic review and possibly a meta-analysis on the prevalence, associated factors and maternal/fetal outcomes of iron deficiency anaemia among pregnant women with SCD. Methods and analysis: We will search the following electronic databases for studies on the iron status of pregnant women with SCD: PubMed, MEDLINE, EMBASE, Google Scholar, African Journals Online, African Index Medicus, Popline and the Cochrane Library. After the selection of eligible studies from the search output, review of full text, data extraction and data synthesis will be performed. Studies obtained from the review shall be evaluated for quality, risk of bias and heterogeneity. Appropriate statistical methods shall be used to pool prevalence estimates for matching studies globally and in subpopulations. This protocol has been reported as per the 2015 guidelines of the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. Ethics and dissemination: There is no requirement for ethical approval as the proposed study will use published data. The findings of this study will be published in a peer-reviewed journal and will be presented at conferences. Trial registration number: CRD42018109803.